A Unified Approach to Determining the Effective Physicomechanical Characteristics of Filled Polymer Composites Based on Variational Principles; Mechanics of Composite Materials; Vol. 54, iss. 6 - Bochkareva S. A. Svetlana Alekseevna; Grishaeva N. Yu. Nataljya Yurjevna; Lyukshin B. A. Boris Aleksandrovich; Lyukshin P. A. Petr Aleksandrovich; Matolygina N. Yu. Nataljya Yurjevna; Panin S. V. Sergey Viktorovich; Reutov Yu. A. Yury Anatoljevich (2019, 2019)
Title screen